2016
DOI: 10.1002/ptr.5713
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Trans‐cinnamaldehyde and Eugenol in Reducing Acinetobacter baumannii Adhesion to and Invasion of Human Keratinocytes and Controlling Wound Infection In Vitro

Abstract: The study investigated the efficacy of two natural, plant-derived antimicrobials (PDAs), namely trans-cinnamaldehyde (TC), and eugenol (EG) for decreasing Acinetobacter baumannii adhesion to and invasion of human keratinocytes (HEK001). Moreover, the efficacy of two PDAs for inhibiting A. baumannii biofilm formation was determined using an in vitro collagen matrix wound model. Additionally, the effect of TC and EG on A. baumannii biofilm architecture was visualized using confocal scanning microscopy. Further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Further, extracts of medicinal plant Holarrhena antidysenterica with Conessine increased susceptibility of extensively drug resistant A. baumannii to novobiocin and rifampicin ( Siriyong et al, 2016 ). Additionally, no cytotoxic effects on human epithelial cells at the tested concentrations were reported previously with TC and EG ( Amalaradjou et al, 2010 ; Karumathil et al, 2016 ). Moreover our previous studies revealed that in-feed supplementation of TC and EG in broiler chicks ( Kollanoor-Johny et al, 2012 ) and TC in mice ( Narayanan et al, 2017 ) for 10 days did not result in any toxicity.…”
Section: Discussionmentioning
confidence: 51%
“…Further, extracts of medicinal plant Holarrhena antidysenterica with Conessine increased susceptibility of extensively drug resistant A. baumannii to novobiocin and rifampicin ( Siriyong et al, 2016 ). Additionally, no cytotoxic effects on human epithelial cells at the tested concentrations were reported previously with TC and EG ( Amalaradjou et al, 2010 ; Karumathil et al, 2016 ). Moreover our previous studies revealed that in-feed supplementation of TC and EG in broiler chicks ( Kollanoor-Johny et al, 2012 ) and TC in mice ( Narayanan et al, 2017 ) for 10 days did not result in any toxicity.…”
Section: Discussionmentioning
confidence: 51%
“…Another study performed by Karumathil et al [ 40 ] revealed the in vitro ability of eugenol to reduce A. baumannii adhesion and invasion to human keratinocytes and also to inhibit biofilm formation in an in vitro collagen matrix wound model.…”
Section: Resultsmentioning
confidence: 99%
“…This model was selected based on the known information that wound infections are one of the most significant infections caused by A. baumannii [ 79 ]. Several studies have shown the applicability of topically applied non-antibiotic agents in the treatment of A. baumannii wound infections [ 32 , 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%